2016
DOI: 10.1080/09712119.2016.1141776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of level and source of supplemental tannin on growth performance of steers during the late finishing phase

Abstract: Two trials were conducted to evaluate the effect of tannin supplementation of steers during the feedlot finishing phase. In Trial 1, 96 Holstein steers (478 ± 6.5 kg) were used to evaluate the effects of level of supplemental condensed tannin (0%, 0.2%, 0.4%, and 0.6% of dry matter basis) on growth performance. Supplemental tannin increased (6.5%, P = 0.05) weight gain, gain efficiency (5.5%, P = 0.04), and tended to increase dietary net energy (3.2%, P = 0.06). In Trial 2, 96 Holstein steers (392 ± 4 kg) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 23 publications
1
36
0
2
Order By: Relevance
“…In the past tannins were described as anti-nutritive substance and studied for their anti-nutritional effects which reduced the performance in growing animals (Smulikowska et al 2001;Mueller-Harvey 2006). In contrast, several Authors showed lack of differences, or even increased ones, on the performances of rabbit and other species fed with diets supplemented by tannins (Liu et al 2009;2011;Omnes et al 2017;Rivera-M endez et al 2017). Similar results were observed by Liu et al (2009) in rabbits fed with chestnut tannins who hypothesised that the reason might be related to the small amount of tannins supplemented in the diet.…”
Section: Resultsmentioning
confidence: 99%
“…In the past tannins were described as anti-nutritive substance and studied for their anti-nutritional effects which reduced the performance in growing animals (Smulikowska et al 2001;Mueller-Harvey 2006). In contrast, several Authors showed lack of differences, or even increased ones, on the performances of rabbit and other species fed with diets supplemented by tannins (Liu et al 2009;2011;Omnes et al 2017;Rivera-M endez et al 2017). Similar results were observed by Liu et al (2009) in rabbits fed with chestnut tannins who hypothesised that the reason might be related to the small amount of tannins supplemented in the diet.…”
Section: Resultsmentioning
confidence: 99%
“…Feeding tannins can promote protein degradation and improve the flow of metabolizable amino acids to the small intestine (Min, Barry, Attwood, & McNabb, ). However, depending of the dietary concentration, tannins may be toxic and can reduce nutrient digestibility (Orlandi, Kozloski, Alves, Mesquita, & Ávila, ; Rivera‐Méndez, Plascencia, Torrentera, & Zinn, ). When ingested in moderate amounts (5% DM), condensed tannins interact with proteins in the saliva, improving the digestive use of proteins that are protected against excessive ruminal degradation, reducing production of methane gas (Makkar, ; Vasta & Luciano, ), and inhibiting ruminal microorganism activity (Cação et al., ) by interfering with the biohydrogenation (BH) process (Vasta, Makkar, Mele, & Priolo, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the studies of ruminant, 71.3 g/kg total tannin improved the body weight gain and feed conversion ratio in Holstein bulls (25). This may be because, tannin-protein complexes are less soluble and less accessible to proteolytic enzymes in the ruminal pH, and thereby reduce the degradation of proteins in the rumen and increased the degradation of proteins in the intestine (26). These results revealed dosagedependent and species-special effect of tannin.…”
Section: Introductionmentioning
confidence: 91%